Chapter Sulla geograficità della ecologia storica: contributi di Massimo Quaini - Moreno, Diego (Territori, 2021)
The paper identifies the main contributions of Massimo Quaini to the problems of historical ecology in its South-European developments and to the definition of geographic-historical microanalysis within geography. It is on this ground that the work of the naturalists/ecologists has most dialogued with his geographical epistemology, starting from the dissatisfaction with the macro-categories of the global scale, the decontextualization of geographic facts and the problems of the "second biologization of the environment", and drawing new perspectives for geographical action starting from the interpretation of rural and historical-environmental heritage.